(untitled) (Intersections of Faith and Culture: American Journal of Religious and Cultural Studies (2993-2599), 2025)
This research investigates the impact of translation on legal and social justice in the United States, focusing on how linguistic mediation shapes access to rights, equality before the law, and fair treatment across diverse communities. Despite the growing body of scholarship on language access, a significant research gap remains regarding the intersection of translation, legal frameworks, and social justice outcomes. This study introduces a novel contribution by examining translation not only as a technical linguistic practice, but also as a socio-legal mechanism that affects marginalized populations, especially immigrants, asylum seekers, and linguistic minorities. Drawing on socio-legal theories, critical translation studies, and access-to-justice frameworks, the research explores the ways in which translation practices either reinforce or challenge structural inequalities. The findings have profound implications for legal policy, court interpretation standards, and social equity initiatives. Ultimately, this study contributes to bridging the gap between translation studies and social justice scholarship, offering both theoretical advancements and practical recommendations for policy reform.